Neapolis Scythica – Simferopol – Test Excavations 1993 - Rudolph, Wolf; Fotiadis, Michalis (Journal of Hellenistic Pottery and Material Culture, 2017)
For various reasons this publication was delayed. Meanwhile, though, archaeological work in the Black Sea area has continued, and that with increased vigour. To mention only a few bench-marks: in the wake of the deep-rooted changes in the Eastern-Block system, at the end of the 20th century and during the ﬁrst years of this millennium alone three dedicated research-centres were founded, one German, one American, and one Danish. These are the Zentrum für Archäologie und Kulturgeschichte des Schwarzmeerraumes‹ (ZAKS) at the University of Halle-Wittenberg in 2000, the ›Centre for Black Sea Studies‹ at Aarhus University in 2002 and in 2004 the ›American Research Centre in Sofia‹ (ARCS). Among state-funded institutions, the Eurasian department of the DAI of 1995 has an extraordinary scope which sweeps over all of Asia.